Preferences of Ukrainian Agribusinesses Toward Sustainability Reporting for Financing of Green Recovery - Metelytsia Volodymyr; Gottlieb Uliana; Brosig Stephan; Gagalyuk Taras (Zagadnienia Ekonomiki Rolnej)
Sustainability financing is a promising instrument for the recovery of Ukrainian agriculture during and after the war, particularly in light of Ukraine’s closer integration with the European Union. This study is the first of its kind to assess the opportunities for establishing institutional foundations for sustainability finance markets in Ukraine. Moreover, in the context of the EU Green Deal, this study provides pioneering evidence on the aspects that policy frameworks should consider to address the generally underdeveloped area of sustainability reporting in primary agriculture.